Urgensi Pembaharuan Undang-Undang Desa (Undang-Undang Nomor 6 Tahun 2014) Terkait Standarisasi Implementasi Kebijakan Tata Ruang Desa - Endriyani Lestari (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
The Village Spatial Plan (RTRW) is a follow-up interpretation of the District RTRW. These provisions have been stated separately in the Village Law. However, in practice, standardization of village spatial policy implementation has not been fully implemented. The concept of village development needs to pay attention to village spatial planning to ensure the benefits and compliance of existing regulations. The method applied in this study is the normative juridical method through qualitative review. Normative juridical review is a stage of legal review carried out through the review of library sources or secondary information as the main material by conducting research related to the problem under study. The results of this study show that to implement policies related to village spatial planning, there are two possible factors, namely supporting and inhibiting factors. To develop clarity on the objectives of policy implementation, legal certainty is needed that can accommodate the needs of village structuring and control.